Jacob Mincer Award (Journal of Labor Economics, 2020)
Previous articleNext article FreeJacob Mincer AwardPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreRichard Blundell is the 2020 recipient of the Jacob Mincer Award for lifetime contributions to the field of labor economics. Blundell is the David Ricardo Professor of Political Economy at University College London and the director of the Economic and Social Research Council (ESRC) Centre for the Microeconomic Analysis of Public Policy at the Institute for Fiscal Studies. He is a fellow of the Society of Labor Economists, the Econometric Society, and the British Academy; an honorary member of the American Academy of Arts and Sciences; and a foreign associate of the National Academy of Sciences. Richard has won numerous prizes and awards, including the Frisch Medal of the Econometric Society, the Institute of Labor Economics (IZA) Prize in Labor Economics, the Nemmers Prize in Economics, and the BBVA Foundation Frontiers of Knowledge Award. In 1995 Richard received the Yrjö Jahnsson Award for the best young economist in Europe from the European Economic Association, and in 2014 he received a knighthood for his services to economics and social sciences. Richard has served as coeditor of the Journal of Econometrics and Econometrica and as president of the European Economics Association, the Econometric Society, the Society of Labor Economists, and the Royal Economic Society.Richard was born in Shoreham-by-Sea, England, and took his undergraduate degree in economics and statistics at the University of Bristol. After completing his MS at the London School of Economics, Richard joined the faculty at the University of Manchester, where he remained for 10 years. In 1984 he was appointed to the David Ricardo Chair at University College London, where he has subsequently taught and mentored many generations of graduate students and junior faculty. From 1986 to 2016 he was also research director at the Institute for Fiscal Studies.From his earliest published papers Richard’s work has been focused on using economic theory and econometric methods to model and understand individual choices and to help inform policy making on issues such as taxation, pensions, training programs, and innovation policy. His work has provided an integrated treatment of consumption and employment decisions to estimate labor supply elasticities, to analyze the effects of tax reforms, and to help explain the divergence between income and consumption inequality. Richard has also made many fundamental contributions to econometric methodology, including the development of new methods to address endogeneity in censored and limited dependent variable settings and for estimating dynamic panel data models.In a series of innovative papers spanning more than 40 years, Richard has investigated the joint behavior of consumption and labor supply and has emphasized to the profession the insights that can be gained only by examining the two together. His papers on the retirement savings puzzle with James Banks and Sarah Tanner, on consumption inequality and partial insurance with Luigi Pistaferri and Ian Preston, and on collective labor supply with Pierre-Andre Chiappori, Thierry Magnac, and Costas Meghis all build on this important theme.Throughout his career Richard has also focused on the important role that careful economic modeling, combined with cutting-edge econometric methods, can play in the analysis of labor market policies such as training and welfare-to-work programs. His papers on the Working Family Tax Credit program and the New Deal training program for youths are exemplars of this approach.In light of Richard’s long series of important contributions to the theory and practice of applied economics, his generous support and mentoring of young economists, and his key roles in the profession and on numerous government advisory boards and commissions, he is an outstanding and truly worthy recipient of the Jacob Mincer Award.2020 Nominating Committee:Katherine Abraham (ex officio)David Card (chair)Daron AcemogluHilary HoynesJennifer HuntAlexandre MasBarbara Petrongolo Previous articleNext article DetailsFiguresReferencesCited by Journal of Labor Economics Volume 38, Number 3July 2020 Published for the Society of Labor Economists, Economics Research Center/ NORC Article DOIhttps://doi.org/10.1086/709476 © 2020 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.